Environmental change, human security and ASEAN's response - Azhana binti Mohamad (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
Located in a disaster-prone area, Southeast Asian region has experienced more than 3000 natural disasters for the past 25 years. The most deadly natural disasters in the Southeast Asian history were Cyclone Nargis in 2008 and Indian Ocean Tsunami in 2004 which claimed more than 300,000 lives. In relation to this, this study highlights three major issues related to environmental change which have affected human security in Southeast Asia namely, climate change, natural disasters, and haze pollution. This study is based on analyses of documents. For data on the extent and impact of environmental change, most sources were from Intergovernmental Panel on Climate Change (IPCC), Economic and Social Commission for Asia and the Pacific/International Strategy for Disaster Reduction (ESCAP/ISDR) and Asian Development Bank (ADB). This study finds that the occurrence of natural disasters has been triggered by climate change. It concludes that human security in the region is threatened by death of people, infectious diseases, food insecurity and vulnerability of livelihood and safety of common people as a result of climate change, natural disasters, and haze pollution. There is also a longer term effect on human security and development as a result of climate change. Human security threats which are transnational in nature have forced ASEAN to compromise its non-interference policy and the ASEAN Way.